CATHERINE OF BEDIA: A FEMALE TO THE CRIMINAL JUSTICE. THE INDIVIDUAL AND HIS COMMUNITY IN A CANTABRIC VILLAGE IN THE LATE FIFTEENTH CENTURY (BILBAO). - Muñoz Saavedra, Eduardo (Revista de Historia Social y de las Mentalidades, 2016)
This article aims to analyze, from different  perspectives, the presence of a woman in  the Spanish royal criminal documentation in  the late fifteenth century. Thus, it serves and  reflects around various elements that explain  the relationship between Catherine of Bedia,  a woman from Bilbao village identified as a  criminal, and the different spaces and levels of  socialization in which she is inserted. In this way,  in the first place, historical forces that converge  to the existence of royal criminal documents are  analyzed; on the other hand, the criminal actions  of Catherina are reconstructed, considering  her movement, the sense of space, the criminal  association and the actions of the court. All that  with the purpose of reach, not just the scope of  female crime, but the everyday of villain life and  their dynamics, structures, and local and global  points of inflection.
Keywords: Woman; Royal criminal justice; Villain society